ASURANSI DAN PENGGADAIAN DALAM PERSPEKTIF ISLAM - Khasanah, Uswatun (Universitas Islam Negeri Raden Intan Lampung, 2014)
The question of insurance is a major concern ofcontemporary Islamic jurisprudence. Insurance is animportant part of the modern business environment.Many scholars criticize the system of conventionalinsurance as exploitative and unjust. They point out thatpaying money for something, with no guarantee ofbenefit, involves high ambiguity and risk. One pays intothe program, but may or may not need to receivecompensation from the program, which could beconsidered a form of gambling. The insured always seemsto lose while the insurance companies get richer andcharge higher premiums. On the other hand, there arescholars who argue that the insurance contract contains agreat deal of gharar that makes the contract invalid. Theseargue that this gharar shall be forsaken if we change thestructure of the insurance contract in question, making ita cooperative that receives premiums as donations. Basedon this argument, Islamic insurance companies arefounded. The purpose of this article is to discuss furtherabout this issue.